AB Initio (DFT) and Vibrational Studies of the Synthesized Heterocyclic Compound 2-6-oxo-2-Thioxotetrahydropyrimidin-41H-Ylidene Hydrazine Carbothioamide - Kalaiarasi, N.; Manivarman, S. (Journal of New Developments in Chemistry, 2017)
The structure of the newly synthesized hydrazone derivative 2 - 6 – oxo - 2-thioxotetrahydropyrimidin – 4 1H - ylidene hydrazine carbothioamide (OTTHPYHCT)compound is determined by using spectral information and elemental study. Density functional theory (DFT) studies were performed using the B3LYP/6-31G (d, p) basis set to expand imminent into their structural properties. Frontier molecular orbital (FMO’s) analysis of title compoundwas computed at the same level of theory to get knowledge about their kinetic stability of the molecule by the energy gap value obtained. Global reactivity descriptors are determined to explain the biological activity of the molecule. NBO analysis provides information about charge transfer, delocalization effect, hyperconjugative interactions and the energy responsible for the stabilization of the compound. First hyperpolarizability analysis nonlinear optical response was simulated at the B3LYP/6-31G d, p level of theory as well. Thermodynamic parameters explain vibrational intensity of the molecule.
Keywords: Hydrazine; carbothioamide; DFT; FMO’s; NLO; NBO; Thermal parameters